TATANAN UPACARA MEMBANGUN â€œPAUMAHANâ€ - Ida Bagus Gde Manuaba (Universitas Dwijendra, 2014)
In the context within developing for the traditional housing is not very complicated if we search its meaning related to find out the happiness for all, in realistic and religious term. All traditional housing development steps have to be followed by a specific process contucted by ritual acticity, such as : nyakap palemahan, nasarin dan melepas.The article is a library research by selecting some related literatures using content of analysis method. From the literatures above the similar content are confirmed andinducted and finally the cinclusion is a categorization of contents. The result show that ther are two otems regarding research problemto be anwered, those are : (i) the steps and way in the traditional process developing consist of : (i) ngaskara process and its offering, (ii) the offering gradual depends the economical and social level.